MARKETING PERFORMANCE DETERMINANT OF HALAL PRODUCTS IN INDONESIA - Aan Nasrullah (State Institute of Islamic Studies (IAIN) Palu, 2019)
Abstract. The aims of this study are (1) To find out and analyze the factors that contribute greatly to the performance of marketing halal products, (2) To find out and analyze marketing performance factors that have the most dominant multiplier effect on the development of halal products in Indonesia. The data analysis technique used is Confirmatory Factor Analysis (CFA). The results of this study show that based on the results of the analysis with the CFA method there are five independent variables that have a contribution to the dependent variable. First the Product Competition Level variable with a correlation value of 0.920. Second, HR Marketing Performance variable which has a correlation value of 0.895. Third, Infrastructure variables with a correlation value of 0.873. Fourth, Amount of Distribution Cost with a correlation value of 0.741, as well as the five variables X3, namely Market Competition Level variables with a correlation value of 0.572. Correlation value-of the five variables shows a strong relationship between the five independent variables with the performance variable of marketing halal products. From a number of marketing performance factors formed through literature review and after analysis using the CFA method, product competition variables are variables that have a correlation value of 0.920. The matrix component value shows a strong correlation between product competition variables and the performance of halal product marketing. The correlation value is greater than the other four independent variables. Keywords: marketing performance, halal products, confirmatory factor analysis